Laparoscopic nephrectomy for xanthogranulomatous pyelonephritis: are there predictive factors for success? (Clinics, 2012)
OBJECTIVES: Laparoscopic nephrectomy for xanthogranulomatous pyelonephritis is currently associated with great operative difficulty and surgical complications. Herein, we report on our single-center experience and describe predictive factors for successfully accomplishing this procedure. METHOD: Between March 1998 and April 2010, 66 patients (27 men and 39 women) underwent laparoscopic nephrectomy for the treatment of a unilateral nonfunctioning kidney. These patients had previous diagnoses of renal chronic inflammation associated with calculi and previous pyonephrosis. All of the nephrectomies were performed using the transperitoneal approach, and a similar technique was used for radical nephrectomy. RESULTS: Laparoscopic nephrectomy for the treatment of renal chronic inflammation was successful in 58/66 cases (87.9%). Eight cases were converted to the open technique because of difficulty in progression, which was related to the discovery of dense adhesions in the hilar or perirenal region. One major (colonic lesion) and two minor (wound infection) complications occurred in the conversion group. A diagnosis of xanthogranulomatous pyelonephritis was confirmed pathologically for all of the specimens. Of the factors examined, a longitudinal renal length greater than 12 cm (laparoscopy group - 7.2±1.8 cm, versus open group - 13.6±1.5 cm; p